The Reinvigoration of Pesantren Pedagogy in Shaping the Adaptive Character of An-Nawawi Students in the Society 5.0 Era - Madum, Mohamad; Raharjo, Raharjo; Awanis, Atsmarina; Mujahid, Ahd. (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
The aim of this study is to analyze and formulate a revitalization strategy for pesantren pedagogy to shape students who are adaptable in the Society 5.0 era, whilst remaining rooted in the values and traditions of Pesantren An-Nawawi Berjan Purworejo. This study employs a qualitative approach using a case study design; data is classified into primary and secondary data. Primary data consists of information and actions obtained directly from key informants, while secondary data includes written documents. Data is collected through observation, interviews, and documentation. Data analysis uses an interactive model that includes data collection, data condensation, data presentation, and a conclusion drawn, and is tested for validity through triangulation of sources and techniques. The results of the study show that pesantren pedagogy based on habituation, example, and a 24-hour life system is effective in forming religious character and discipline, but has not fully developed cognitive adaptivity and digital literacy. Existing values, learning practices, and pedagogical relationships tend to be normative and hierarchical, so they require transformation. The resulting reactualization model emphasizes the integration between traditional values of Islamic boarding schools, the competency demands of Society 5.0 (digital literacy, collaboration, problem solving), as well as the principles of preserving tradition and innovation. This study concludes that the reactualization of pesantren pedagogy must be integrative and transformative in order to form students with strong character and be adaptive to changing times.